An Optimized and General Synthetic Strategy To Prepare Arylnaphthalene Lactone Natural Products from Cyanophthalides - Kim, Taejung; Jeong, Kyu Hyuk; Kang, Ki Sung; Nakata, Masaya; Ham, Jungyeob (WILEY-V C H VERLAG GMBH, 2017)
A simple method for the preparation of arylnaphthalene lactone natural products was developed and used to synthesize diphyllin (10), justicidin A (12), cilinaphthalide B (13), taiwanin E (15), chinensinaphthol (16), taiwanin E methyl ether (17), chinensinaphthol methyl ether (18), justicidin C (21), and justicidin D (22). Key steps of the syntheses include the Hauser-Kraus annulation of cyanophthalides 7a and 7b and Suzuki-Miyaura cross-coupling reactions between arylnaphthalene lactones that contain a sulfonate group (i.e., 9, 14, 19, and 20) and various potassium aryltrifluoroborates.
Keywords: CROSS-COUPLING REACTIONS; JUSTICIA-PROCUMBENS; 1-ARYLNAPHTHALENE LIGNAN; PHYLLANTHUS-MYRTIFOLIUS; BIOLOGICAL EVALUATION; DERIVATIVES; ANALOGS; BIOEVALUATION; NEOLIGNANS; INHIBITORS